Schwannoma of the colon: a case report and literature review - Alshahrani, Manar Mohammed; Abdelrazek Mohammed Eisa, Ramadan; Oraijah, Abrar Abdullah; Mohammed Saleh Nasief, Bader (International Journal of Research in Medical Sciences, 2024)
Tumours that originate from the Schwann cells are known as schwannomas. Schwannomas are generally rare, but the rarest are perhaps those of the colon and rectum. The areas of the body that ordinarily experience more schwannomas include such organs as the head, neck, arms, and limbs. Although they are mostly usually harmless, malignant degeneration may appear without surgery. The current case study is a male, 40 years of age, who reported abdominal pain and recurrent vomiting and was admitted for elective Esophagogastroduodenoscopy (EGD) and colonoscopy. There was no family history of inflammatory bowel disease or cancer, and he had no prior abdominal surgeries. A physical examination revealed mild tenderness in the right lower quadrant. Results of the examinations indicate normal mucosa and vasculature in visualized parts. One polyp ascending around 1 cm was removed completely by cold snare after elevation by an adrenaline base secured by one clip. Another polyp in the transverse colon, around 1 cm, was removed completely by a hot snare base secured by one clip. Following a routine biopsy test that revealed a polypoid lesion consisting of bland spindle cells with an elongated shape. Upon histological testing, a schwannoma was found. Immunohistochemistry revealed that the tumor was negative for EMA, cluster of differentiation (CD)117, calertinin, and synaptophysin, and positive for S100 and vimentin, with a Ki-67 proliferative index of 3%. There was no lymph nodes implicated. Schwannomas may present difficult biopsy investigations, and a reliable diagnosis of this sickness requires immunohistochemistry. Unlike gastrointestinal stromal tumors, Schwannomas contain vimentin and the S100 protein but are negative for CD117. The likelihood of tumor aggressiveness increases significantly in cases recording a Ki-67 score of ≥5%. As a result, the recommended treatment for schwannomas is oncological drastic surgical excision.